ANALISIS FUNGSI SENI PERTUNJUKAN TEATER SEBAGAI MEDIA KOMUNIKASI DALAM MENYUARAKAN KRITIK SOSIAL: Studi Pada Pertunjukan Teater Koma Lakon J.J Sampah-Sampah Kota Produksi ke-159 - Siti Ainayah (2020)
The development of technology and communication in the era of globalization and digitalisation has led to the birth of a variety of new internet-based communication media that dominate the community. In the midst of exposure to modern communication media which currently tend to pay less attention to objectivity in conveying messages or information, the author tries to analyze the function of theater performance as a conventional communication media that is considered capable of criticizing phenomena in a neutral manner without riding on interests and leading public opinion in voicing social criticism. The object of the research will be conducted at one of the independent theater groups in Indonesia, namely Teater Koma in its performance which contains an element of criticism with the title J.J Sampah-Sampah Kota. The purpose of this research is to analyze the function of theater performance arts as a communication medium, in line with this, this research will also look at how Teater Koma group packs and pours messages containing elements of social criticism through theater performances. This type of research is a qualitative study using a descriptive approach and case study method, where data collection techniques will be obtained from observations, documentation, and interviews with five data sources. Supported by the concept of art communication, the results of the study show that the existence of theater performance art in the midst of the current era has performed a dual agenda function, where theater performances do not only function as mere entertainment media, but their existence as communication media also contributes to carrying out social control functions. namely by criticizing phenomena or events that occur in the community. Based on the results of the study, it was concluded that the function of theater performances as a medium of communication to convey criticism is basically considered capable of representing people's aspirations objectively, but it needs to be recognized that the theater function has not been able to compete with the effectiveness and efficiency of online media, especially in reaching audiences and meeting information needs as well as community entertainment in the current era.